Formation of carbon coated yolk-shelled Fe3O4-CeO2 hollow spheres toward remarkable performance supercapacitors. (October 2022) - Wei, Chengzhen; Yu, Zhaojiang; Guo, Zhencai; Guan, Nan; Xing, Wen; Du, Weimin; Liu, Lin; Zhang, Yongming; Cheng, Cheng
Abstract: Yolk-shelled hollow structures with unique structural features are incredibly attractive for energy storage systems. Here we present a self-template strategy to prepare carbon coated yolk-shelled Fe3 O4 -CeO2 hollow spheres. First, yolk-shelled Fe-Ce glycerate precursors are designed by a solvothermal method. Afterward, the carbon coated yolk-shelled Fe3 O4 -CeO2 hollow spheres are eventually synthesized via calcinations the obtained precursors in Ar. Such unique structures endow the Fe3 O4 -CeO2 with abundant inner cavities, large surface area and more electroactive site. As electrode material for supercapacitors, a large capacity of 430 C g −1 is obtained at 2.0 A g −1, and it can be as high as 198.4 C g −1 even at 20 A g −1 . Moreover, it also takes outstanding rate capability and superior cycling durability (only 5.2 % capacity reduction over 5000 cycles at 6.0 A g −1 ). Furthermore, a quasi-solid-state flexible asymmetric supercapacitor device is constructed by Fe3 O4 -CeO2 cathode and activated carbon anode. The device manifests a high energy density of 46.6 Wh kg −1 at 2.0 A g −1 ( versus 1650 W kg −1 power density). Even at 15 A g −1, the energy density is still 21 Wh kg −1 with 12, 441 W kg −1 . We envision that this work not only explores a promising electrode material for supercapacitors, but also provides an alternative avenue to prepare yolk-shelled hollow structures toward energy storage applications. Graphical abstract: Carbon coated yolk-shelled Fe3 O4 -CeO2 hollow spheres are prepared via a self-template route. Such structural and compositional advantages enable the Fe3 O4 -CeO2 to exhibit remarkable performance in supercapacitors. Unlabelled Image Highlights: Carbon coated yolk-shelled Fe3 O4 -CeO2 hollow spheres are prepared via a self-template route. The prepared Fe3 O4 -CeO2 exhibits remarkable performance in supercapacitors. A quasi-solid-state flexible asymmetric supercapacitor device possesses large energy and power density.